LECTURERS PERCEPTION OF IM/POLITENESS OF STUDENT’S TEXT MESSAGE - Titik Ceriyani Miswaty (Humanitatis : Journal of Language and Literature, 2019)
This research aims at investigating the lecturer’s perception of im/politeness of student’s text message (WhatsApp messages) the data was collected in three stages, including authentic student WhatsApp message, questionnaires and interviews, the main source of data were five lecturers who teaches in the first semester. The data of this research was the text message send by first grade students of IKIP Mataram 2018/2019 to their lecturers during the first semester. There were 200 text messages that have been collected in this research. Since the data was analysed and interpreted in the form of words, phrases and sentences, this research employs the qualitative method. From the data analysis, it was found that there are two types of text messages that mostly appeared, questioning and request. For request message, student’s impoliteness was counted 5% out of 200 text message. While in questioning, the percentage of impoliteness text messages was shown higher than in request, it was 30% out of 200 text messages. Although there were some impolite text messages that were sent by students, the percentage of polite text messages were still being the highest among all categories. This shows us that, there are still many students who use polite language than those who don’t.